Experimental and finite element analysis studies of a reduction-force reducing traction method for pelvic fracture surgeries - Jixuan Liu; Ke Xu; Chunpeng Zhao; Gang Zhu; Yu Wang; Xinbao Wu; Wei Tian (Medicine in Novel Technology and Devices, 2022)
Pelvic fracture is among the most complicated fractures in traumatic orthopedics, with high mortality and morbidity rates. The main difficulty associated with the reduction surgery is significant muscle resistance. It then becomes necessary to decrease the reduction force against this strong muscle resistance, for improving surgical safety. Here, we propose a novel traction method for decreasing the reduction force during pelvic reduction, and investigate the performance of the elastic traction method on decreasing the reduction force using experimental tests and simulation-based analyses. From the experimental results, the reduction force decreased by 59.2% when 10 ​kg of elastic traction was applied. We also establish a musculoskeletal model of the pelvic fracture reduction, for analyzing the muscle resistance and the optimal traction force applied in reduction surgeries. The elastic traction method can counteract the muscle resistance increase in the non-traction direction owing to its flexibility. We conclude that the optimal traction force applied should be in the 10–15 ​kg range, and recommend adopting a dynamic traction strategy rather than continuous traction in clinical settings. Elastic traction is very promising for various surgeries that require traction, including pelvic reduction. It significantly reduces force, which can significantly reduce the physical exertion of the operating surgeon, the possibility of additional injuries to the operated patient, and promotes robot-assisted reduction surgeries.